Aerobic Exercise Training Prevents Perivascular Adipose Tissue-Induced Endothelial Dysfunction in Thoracic Aorta of Obese Mice - Sousa, Andressa S.; Sponton, Amanda C. S.; Trifone, César B.; Delbin, Maria A. (Frontiers in Physiology, 2019)
Background: The mechanisms underlying the perivascular adipose tissue (PVAT) dysfunction in obesity are closely related to inflammation and oxidative stress. The present study aimed to investigate the effects of aerobic exercise training on PVAT-induced endothelial dysfunction of thoracic aorta of obese mice. Methods: Male mice C57BL6/JUnib (6-7 weeks) were divided into: sedentary (c-SD), trained (c-TR), obese sedentary (o-SD) and obese trained (o-TR). Obesity was induced by 16 weeks of high-fat diet and exercise training of moderate intensity started after 8 weeks of protocol and was performed on a treadmill, 5 days/week, for more 8 weeks, 60 minutes per session. The vascular responsiveness was performed in thoracic aorta in the absence (PVAT-) or in the presence (PVAT+) of PVAT. We analyzed circulatory parameters, protein expression, vascular nitric oxide (NO) production and reactive oxygen species (ROS) in PVAT. Results: The maximal responses to acetylcholine (ACh) were reduced in PVAT+ compared with PVAT- rings in the o-SD group, accompanied by an increase in circulating glucose, insulin, resistin, leptin, and TNF-. Additionally, the protein expression of iNOS and generation of ROS were increased in PVAT and production of vascular NO was reduced in the o-SD group compared with c-SD. In the o-TR group, the relaxation response to ACh was completely restored, the circulatory TNF-, iNOS protein expression and ROS were normalized with increased expression of Mn-SOD in PVAT, resulting in enhanced vascular NO production. Conclusion: The PVAT induced endothelial dysfunction in thoracic aorta of obese mice, associated with circulatory inflammation and oxidative stress. Aerobic exercise training up-regulated the anti-oxidant expression and decreased PVAT oxidative stress with beneficial impact on endothelium-dependent relaxation.